Requisitos de Software para o Design de Aplicativos Gamificados para Gestão de Tempo e Tarefas para Crianças e Adolescentes com TDAH - Gomes, Tássio José Gonçalves; dos Santos, Wilk Oliveira; Marques, Leonardo Brandão; Brito, Patrick Henrique da Silva; Bittencourt, Ig Ibert (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2019: Anais do XV Simpósio Brasileiro de Sistemas de Informação, 2019)
Attention Deficit Hyperactivity Disorder has been one of the most studied topics in school-age children in face of their day-life difficulties. At the same time, gamification, which uses game mechanics in a non-game context, is an used strategy to engage people in reaching their goals in different contexts. Thus, this paper aims to present software guidelines for the design of gamified educational technologies to patients with this deficit. The requirements were compiled based on the results of a study conducted with parents, psycho-pedagogues, psychologists and speech therapists. Two main guideline categories were found: (i) behavioral strategies and (ii) gamification elements used, the first being composed of 17 strategies and the second by 12 gamification elements. From these categories and data analysis, 16 system requirements were proposed for the development of gamified applications to people with Attention Deficit Hyperactivity Disorder.